School TV as a Learning Media in Improving Listening Skills in Early Childhood - Ari Wulandari; Shofa; Eka Sri Pujianti; Hasmira; Sri Watini (Universitas Panca Sakti Bekasi, 2024)
Digital media innovation as one of the indispensable techniques in the modern era 4.0 has developed rapidly and fluctuated affecting various parts of life in all circles, including the world of early childhood. One of the influential parts of life is language. During the pandemic, children have a lot of time with digital media. So, without realizing it, this has a huge impact on children's language development. Currently, there is one media that can answer this need, namely digital media School TV. Children, parents, and teachers can utilize the